A case report of pulmonary arterial hypertension in pregnancy and complications of anticoagulation therapy. Issue 32 (August 2018) - Xiang, Yangfang; Li, Jun; Sun, Yinxiang
Abstract: Rationale: Treprostinil, a potent vasodilator, is the treatment of choice for severe pulmonary arterial hypertension (PAH) during pregnancy. Its inhibition of platelet aggregation increases the risk of hemorrhage. In addition, anticoagulation therapy is widely used in pregnancy with PAH due to the hypercoagulable state. However, very little is known about the complications of anticoagulants' use in pregnancy with PAH. Patient concerns: A 27-year-old pregnant woman was admitted to the hospital at 32weeks with progressive dyspnea. Diagnoses: The pregnant was diagnosed with ventricular septal defect 12 years prior to presentation. Combining clinical manifestation with results of right heart catheterization (RHC) and echocardiography, it was consistent with severe World Health Organization (WHO) group I PAH. Interventions: Supportive treatment included supplemental oxygen, intravenous treprostinil, sildenafil and prophylactic anticoagulation. Outcomes: Gastrointestinal bleeding is occurred in our patient when dalteparin were used in conjunction with treprostinil. Her care was further complicated refractory to usual conservative measures before delivery. Lessons: This case report illustrates the complexities that arise when prostacyclin therapies are combined with necessary anticoagulation in patients with PAH during pregnancy. More intention should play to the complications of anticoagulant in pregnancy with PAH during treprostinil therapy.